2021
DOI: 10.1002/cjce.23947
|View full text |Cite
|
Sign up to set email alerts
|

Gelation kinetics of functionalized silica crosslinked polymeric gels used in conformance control applications

Abstract: The potential crosslinking of three types of nitrogen-containing functionalized silica (TAAcONa, guanidine, and triamine) with polyacrylamide (PAM) has been investigated. Only triamine silica was able to crosslink with PAM, producing barely flowing gel with storage modulus of around 700 Pa. Micro differential scanning calorimeter (μDSC) analysis illustrated exothermic peaks indicating crosslinking of PAM with triamine and polyethyleneimine (PEI), with crosslinking onset temperatures of 80 C and 84 C. TGA analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Comparing the similarities in the chemistry of chitosan and PEI, it is speculated that both crosslinkers undergo the same crosslinking mechanism with PAM. Figure agrees with the above statement as the application of PEI was reported to be limited to the high-temperature reservoirs when the temperature exceeds 80 °C. , Overall, the gel strength was observed to increase with the temperature, which is suggested to be caused by the increasing crosslinking due to the acceleration in the degree of hydrolysis in PAM at high temperatures.…”
Section: Resultssupporting
confidence: 88%
“…Comparing the similarities in the chemistry of chitosan and PEI, it is speculated that both crosslinkers undergo the same crosslinking mechanism with PAM. Figure agrees with the above statement as the application of PEI was reported to be limited to the high-temperature reservoirs when the temperature exceeds 80 °C. , Overall, the gel strength was observed to increase with the temperature, which is suggested to be caused by the increasing crosslinking due to the acceleration in the degree of hydrolysis in PAM at high temperatures.…”
Section: Resultssupporting
confidence: 88%
“…Compared with PAM/PEI gels, PAM/TAS has higher salt resistance. Shamlooh et al 116 investigated three functionalized SiO 2 with nitrogen-containing functional groups, sodium triamine tetraacetate (TAC), guanidine, and triamine. The results showed that only triamine-SiO 2 could cross-link with PAM with an elastic modulus of about 700 Pa.…”
Section: Improved Gel Strengthmentioning
confidence: 99%
“…[10] This pressure is enough to keep water in the liquid phase as per our previous literature reports, and the selected strain was in the linear viscoelastic range. Al-Muntasheri et al [11][12][13] PAM/Cr +3 3-8 days 65-80 C Relatively toxic compared to other crosslinkers.…”
Section: Rheological Characteristicsmentioning
confidence: 99%